Connecting urban food plans to the countryside: leveraging Denver's food vision to explore meaningful rural-urban linkages - Jablonski, Becca B. R., author; Carolan, Michael, author; Hale, James, author; Thilmany McFadden, Dawn, author; Love, Erin, author; Christensen, Libby, author; Covey, Tabitha, author; Bellows, Laura, author; Cleary, Rebecca, author; David, Olaf, author; Jablonski, Kevin E., author; Jones, Andrew S., author; et al. (Colorado State University. Libraries, 2019)
Cities are increasingly turning to food policy plans to support goals related to food access, food security, the environment, and economic development. This paper investigates ways that rural farmers, communities, and economies can both support and be supported by metropolitan food-focused initiatives. Specifically, our research question asked what opportunities and barriers exist to developing food policies that support urban food goals, particularly related to local procurement, as well as rural economic development. To address this question, we described and analyzed a meeting of urban stakeholders and larger-scale rural producers related to Colorado’s Denver Food Vision and Plan. We documented and explored “findings” gleaned from a supply chain diagraming and data compilation process that were then used to inform an event that brought together diverse supply chain partners. Three findings stand out. First, facilitating dialog between urban food policymakers and rural producers to understand potential tensions, mitigate such tensions, and capitalize on opportunities is essential. Second, perceptions and expectations surrounding “good food” are nuanced—a timely finding given the number of preferred procurement programs emerging across the county. Third, critical evaluation is needed across a diverse set of value chain strategies (e.g., conventional and alternative distribution) if food policy intends to support heterogeneous producers, their communities, and urban food policy goals.
Keywords: food policy; urban-rural linkage; local food; farm; rural development